2011
DOI: 10.1177/201010581102000207
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial Evaluating the Efficacy of a Nurse Controlled Analgesia (NCA) Protocol in Post Anaesthesia Care Unit (PACU)

Abstract: Introduction:The purpose of this trial was to determine the efficacy of a Nurse Controlled Analgesia (NCA) protocol in reducing the time taken to achieve a satisfactory postoperative pain score. The safety aspects of the NCA protocol were also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Proceedings of Singapore Healthcare  Volume 20  Number 2  2011 et al reported on how Nurse Controlled Analgesia helped improve efficiency in the provision of pain relief to post operative patients 8 . These are 2 examples among hundreds within SingHealth that have helped improve care to our patients.…”
Section: Moving Forward In Patient-centred Carementioning
confidence: 99%
“…Proceedings of Singapore Healthcare  Volume 20  Number 2  2011 et al reported on how Nurse Controlled Analgesia helped improve efficiency in the provision of pain relief to post operative patients 8 . These are 2 examples among hundreds within SingHealth that have helped improve care to our patients.…”
Section: Moving Forward In Patient-centred Carementioning
confidence: 99%